Vermiculite in the initial development of coffee seedlings in different containers - Jean dos Santos Silva; Amilton Ferreira da Silva; Raphael Pontes Hosken Vieira; Nádia Nardely Lacerda Durães Parrella (Scientific Electronic Archives, 2023)
Coffea arabica L. is responsible for 81% of the coffee cultivation area in Brazil and has great economic and social importance in the regions it is cultivated. Producing vigorous seedlings in a short period of time has become an increasing challenge in coffee growing. Thus, the objective of this study was to evaluate the initial development of seedlings produced in bags and polyethylene tubes with different levels of vermiculite. A 2x5 factorial scheme was used; the factors were: two containers: polyethylene bags (containing standard substrate, subsoil and manure (7:3) and tubes (commercial substrate based on pine bark) and addition of vermiculite, at levels 0%, 10%, 20%, 30% and 40%. In each type of substrate, the respective amounts of vermiculite were added. The variables analyzed were shoot height, root length, stem diameter, number of leaf pairs, shoot and root fresh and dry matter. Based on the results obtained, it was observed that the seedlings produced in polyethylene bags showed higher significant averages for all evaluated parameters, showing greater vigor and initial development than seedlings produced in tubes. The seedlings produced in bags responded positively to the increase in vermiculite for all analyzed parameters, whereas those produced in tubes show the opposite behavior.